PENGARUH PROJECT CITIZEN TERHADAP CIVIC DISPOSITION PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS XI SMA NEGERI 11 KOTA JAMBI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Based on the results of preliminary observations conducted at SMA Negeri 11 Kota Jambi, a problem was identified in the form of low levels of students’ civic disposition, particularly among Grade XI students in the Pancasila Education subject. This study aims to determine the effect of implementing the Project Citizen learning model on students’ civic disposition. The background of this research is based on the importance of developing students’ civic disposition, which is still considered relatively low. This study employed a quantitative approach using a true experimental design. The population consisted of all Grade XI students, with two classes selected as samples: Class XI F4 as the experimental group and Class XI F5 as the control group, with a total of 72 students. Data were collected through the distribution of questionnaires. The obtained data were then analyzed using statistical techniques, namely the independent sample t-test to test the hypothesis. The results of the analysis showed that the value of t-count was greater than t-table (9.568 > 1.666), and the significance value (2-tailed) was 0.000 < 0.05. Based on these results, it can be concluded that the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. Thus, there is a significant effect of the implementation of the Project Citizen learning model on improving students’ civic disposition in the Pancasila Education subject in Grade XI at SMA Negeri 11 Kota Jambi.